Semiótica da vida artificial - Camargo, Carlos Eduardo Pires de (2018)
In the mid 1980’s several bio-inspired approaches emerged to the study of artificial intelligence. Starting from this context and from von Neumann cellular automata, the field of artificial life was developed with the objective to construct artificial systems capable to present similar behaviors to those found in biological phenomena. This thesis recovers the history of artificial life and its relationship with artificial intelligence, presents the difficulties of its development considering cartesian dualism, and demonstrates the possibility of a more adequate way of research based on the hypothesis of continuity between mind and matter, typical of the general semiotics of Charles Sanders Peirce. Through peircean semiotics and using the fundamentals of biosemiotics, the semiotic transposition technique is developed, a set of diagrammatic operations to support the study of artificial life. This technique studies the semiotic processes underlying biological phenomena. Then, through isomorphism, derived from the category theory, a finite automata can be created to computationally express certain aspects of the original biological processes. Throughout the research, the learning and memory behavior of a sea slug species, Aplysia californica, was used as an auxiliary element for the formalization of semiotic transposition. Two other biological phenomena — the genetic translation and the vacancy chain dynamics related to the Pagurus longicarpus, a species of crab — were considered as case studies to demonstrate the general character of the semiotic transposition. It is concluded that the use of semiotic theory as the basis for the study of artificial life constitutes an effective instrument to the creation of bio inspired computational devices